2009
DOI: 10.1557/proc-1160-h14-11
|View full text |Cite
|
Sign up to set email alerts
|

Conformal MOCVD Deposition of GeSbTe in High Aspect Ratio Via Structure for Phase Change Memory Applications

Abstract: We have demonstrated conformal deposition of amorphous GeSbTe films in high aspect ratio structures by MOCVD. SEM analysis showed the as-deposited GeSbTe films had smooth morphologies and were well controlled for void free amorphous conformal deposition. GeSbTe films adhere well to SiO2, TiN, and TiAlN. The morphology and adhesion are stable in 420°C post process. By annealing at 365°C, amorphous GeSbTe films converted into crystalline GeSbTe with polycrystalline grain sizes of 5nm. Film resistivity in the cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Recently, a number of studies have been carried out to investigate the deposition of phase-change materials by ALD and CVD techniques [9][10][11][12][13][14][15]. It has been reported that the precursor and substrates have an important influence on the microstructure and composition of Ge-Sb-Te films.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of studies have been carried out to investigate the deposition of phase-change materials by ALD and CVD techniques [9][10][11][12][13][14][15]. It has been reported that the precursor and substrates have an important influence on the microstructure and composition of Ge-Sb-Te films.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported MOCVD GST films that are conformal, smooth, and have a high density [10][11][12][13]. Our MOCVD GST films can be made to have very low oxygen impurities as shown in Fig.1 and have relatively low carbon and nitrogen incorporation as reported in Ref.…”
Section: Mocvd Gst Filmsmentioning
confidence: 78%
“…[11]. We have made many GST compositions by MOCVD for use in PCM devices [10]. As shown in the GST compositional phase diagram (Fig.…”
Section: Mocvd Gst Filmsmentioning
confidence: 99%
See 2 more Smart Citations